Soziale Integration durch Sport? - Becker, Simone; Häring, Armando (Sportwissenschaft, 2012)
In this study the relationship between physical activity and different dimensions of social integration (number of friends, frequency of contact to friends, number of social contexts the individual is taking part in) is analysed using the data of the Partnermarktsurvey 2009. The concept of opportunities for interaction in foci of activity (here physical activity) is used as the theoretical framework. It can be shown that physical activity has an effect on the social integration of individuals: People who engage in physical activity have more friends, meet them more often and are integrated in more social contexts than people who are not physically active. Differences in social integration even exist among physically active people depending on the kind of sport activity and its form of organisation. Further the setting of the sport activity seems to be of importance. Finally it is recommended that longitudinal data used to investigate the exact causal effect of physical activity on social integration.
Gesehen am 05.11.2018